Enhancing Speaking Skills through Project-based Learning incorporating Monologues - Lyu, Li; Bidin, Siti Jamilah (Forum for Linguistic Studies, 2025)
Speaking skills are pivotal for authentic communication and the ultimate goal of language learning. However, studies on speaking skill in a Chinese local ethnic minority college is relatively scant. Project-based learning (PBL) has increasingly emerged as an efficient method to reinforce the speaking capacities of learners. This study therefore employs a mixed-methods design, combining quantitative study and semi-structured interviews, to evaluate students’language complexity, accuracy, and fluency over four weeks. The employed instruments include speaking tests and semi-structured interviews. The participants (n=60), all of whom were college freshmen majoring in communication media, were divided into an experimental group and a control group, with each group consisting of 30 participants. Paired sample t-tests revealed that PBL combined with monologue tasks significantly improved the students’speaking abilities. Moreover, independent t-tests confirmed that PBL outperformed the Grammar Translation Method. The qualitative findings from the semi-structured interviews highlight improvements in the students’willingness to communicate, critical thinking abilities, and capacity for teamwork. These findings suggest that the combination of PBL and monologue tasks is an effective teaching approach for improving learners’speaking proficiency. Teaching practitioners can incorporate monologues tasks into their teaching practice.